Globalization and Women Empowerment: A Critical Study with Special Reference to India: Examining the Impact of Globalization on Women's Empowerment in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Globalization is a cycle of expanding relationship, interconnectedness and joining of economies and social orders so much that an occasion in one aspect of the globe influences individuals in different pieces of world. Expanding levels of worldwide interconnectedness has influenced the social, financial, and political conditions for ladies in India. The examination endeavours to comprehend the pointers of Women empowerment and the effect of globalization on the ladies of India. This is finished by basically dissecting the effect of globalization on ladies' strengthening. An organized survey with a 5 point Likert scale was controlled on the example. Information was gathered in a deliberate way and was broke down and accordingly gave legitimate deductions. The information has been gathered both from essential just as optional sources. So as to come to trustworthy end results, data has been assembled from working ladies, independently employed ladies and housewives. A complete number of test chose for the investigation were 800 ladies, comprising of 400 each from country and metropolitan zones of India. It has been seen that ladies have been more effective in beating social hindrances by utilizing their abilities. They are turning out to be financially free which prompts have more options about what they do with their lives.